Ophthalmological Outcomes in Patients with Susac Syndrome - Schuknecht, Angelika; Wiest, Maximilian Robert Justus; Said, Sadiq; Bajka, Anahita; Hamann, Timothy; Muth, Daniel Rudolf; Fasler, Katrin; Blaser, Frank; Barthelmes, Daniel; Zweifel, Sandrine (Klinische Monatsblätter für Augenheilkunde, 2024)
Background To report ophthalmological outcomes and treatment regimen in patients with Susac syndrome.Methods This is a retrospective analysis of patients with Susac syndrome treated between November 2015 and March 2023. Multimodal imaging findings, ophthalmic examination data, information on neurological and sensorineural involvement, and therapeutic regimen were reviewed. Visual acuity was recorded as the logarithm of the minimum angle of resolution (logMAR). Ophthalmological manifestations and disease severity were assessed using the previously described clinical activity score (CAS).Results Ten patients with Susac syndrome m : f = 5 : 5 were identified. The mean follow-up time was 31.2 ± 23.3 months (range 1 to 78 months). The mean age was 41.4 ± 13.8 years (range 21 to 59 years). At baseline, corrected distance visual acuity (CDVA) was 0.03 ± 0.08 logMAR. At the last follow-up, CDVA improved to 0.00 ± 0.03 logMAR (p = 0.029). Three of 20 eyes showed an improvement of 5 letters, while no loss of visual acuity was recorded during the follow-up time. Baseline CAS was 10.65 ± 12.69, and CAS at the last follow-up was 5.15 ± 5.49 (p = 0.068). Except for one patient, all were initially treated with intravenous (i. v.) steroids and subsequent oral tapering. Depending on the treatment response, cyclophosphamide (n = 4), i. v. immunoglobulins (IVIGs) (n = 4), anti-CD20 antibodies (n = 3), or plasmapheresis (n = 1) were applied. All patients under treatment for more than 1 month (n = 9) showed improvement in CAS and CDVA.Conclusion Susac syndrome is a rare autoimmune vascular endotheliopathy. Treatment of Susac syndrome appears to result in improving CAS and CDVA. The majority of patients, in addition to the systemic steroids, required systemic immunosuppressive agents. Interdisciplinary communication is crucial to reduce the time to diagnosis and initiation of therapy in patients with Susac syndrome.
Keywords: retina; encephalopathy; arterial branch occlusions; fluorescence angiography; Susac syndrome; immunology